Biosynthesized silver nanoparticles and miR34a mimics mediated activation of death receptor in MCF-7 human breast cancer cell lines - Muhammad Javed Iqbal; Umer Rashid; Zeeshan Javed; Zara Hamid; Komal Imran; Ayesha Kabeer; Shahid Raza; Zainab M. Almarhoon; Željko Reiner; Iulia-Cristina Bagiu; Radu Vasile Bagiu; Ioan Sarac; et al. (figshare, 2022)
Abstract Nano-biotechnology-based clinical applications to cure health-related issues have gained huge attention among the scientific community and hold great promise to limit cancer metastasis. In this study, green-derived silver nanoparticles were synthesized by using leaf extract of Litchi chinensis. Characterization of biosynthesized silver nanoparticles was performed by using UV–Vis spectroscopy, FTIR, XRD, EDS, and SEM analysis. The clinical application of green-drive nanoparticles was investigated by using MCF-7 cancer cell lines. MCF-7 breast cancer cell lines were analyzed against three different treatments. (i) Silver nanoparticles (AgNPs), (ii) miR34a mimics and (iii) Co-delivery of AgNPs and miR34a mimics. Cell viability was determined by MTT assay and, extraction of mRNA and cDNA synthesis were performed after successful cellular transfection. qRT-PCR was done for expression analysis of DR4 and DR5 upon exogenous delivery of all 3 treatments. Results indicate that L. chinensis leaves have a significant amount of phenolic and flavonoid contents and also possess massive antioxidant activity. The diameter of nanoparticles was observed in the range of 41–55 nm. It was concluded that green-derived silver nanoparticles can be a potential contributing agent for cancer prevention and are reported to upregulate the expression of DR4 and DR5 by 0.8-folds and 3.7-folds, respectively.
Keywords: Biochemistry; Space Science; Medicine; Cell Biology; Molecular Biology; Pharmacology; Biotechnology; 39999 Chemical Sciences not elsewhere classified; 69999 Biological Sciences not elsewhere classified; Cancer